Studi Komparasi Pencapaian Aspek Afektif Siswa Antara Yang Aktif Dengan Yang Pasif Pada Proses Pembelajaran Aqidah Akhlaq - Hasan H.A. Buro (PROGRESSA: Journal of Islamic Religious Instruction, 2022)
The purposes of this study are: 1) to know affective students who are active subjects Aqidah Akhlaq. 2) To know affective students who are subjects Aqidah Akhlaq. 3) To know the big difference between active and passive student affective on Aqidah Akhlaq subject. 69 people, in the sampling, of 69 people were taken on the basis of calculation slovinumlah 100% of people as subjects or respondents. In this study the authors use simple linear regression analysis techniques. The conclusions of this research are 1) Observation result observed to 39 respondents following interpretation which got category very clever category 32 and clever number 7, it shows affective nature of students active in MA Hidayatul Muwaffiq Penompo Mojokerto high category. 2) Observation result observed on 30 respondents following interpretation. Respondents who got the category category are very good at 21, pandaiatas 7 and quite high 2 it shows the affective nature of passive students in MA Hidayatul Muwaffiq Penompo Mojokerto enough category. 3) The parametric test to be used in this test is the Mann-Whitney U Test.